Neocolonization of Africa: security-military and economic-investment aspects of instruments of influence of foreign states - V.V.; T.O.; O.S. (Економіка, управління та адміністрування)
The study focuses on the issue of neo-colonization of Africa, identifying the main actors and beneficiaries, as well as their impact on the African region. Two approaches used by foreign states in the process of influencing the African region are singled out: security-military and economic-investment. It was determined that there is a certain correlation between the use of military force and investment activity in the region. The influence of Russian, British, German, French and American private military companies on the countries of the African region is considered. Countries such as the USA and China have advantages in terms of investments and ensuring the security of the governments of African states have several military bases in the region. This is justified by two aspects: the weakness of the governments of African states and the wealth of the region in natural resources. On the other hand, France, due to its inability to pursue an aggressive policy in the African region, actively loses to the propaganda and activities of Russian mercenaries. Lobbying the interests of countries at the UN platform, as shown by the example of voting by countries friendly to Russia, is a rather valuable resource. Therefore, in general, the continent is turning into a battle ground between the West and the East, and it is proven that the West is gradually losing this battle for a new African colonization. Europe and the USA are weak in the struggle for Africa, hoping to win their support with democratic values and investments in the self-sufficiency of African countries. The security-military aspect of the development of Ukrainian-African relations is promising and can solve such issues as providing employment for ex-military personnel and ensuring the national interests of the state.